Aging and the Skeletal Muscle Angiogenic Response to Exercise in Women - Gavin, Timothy P. (J Gerontol A Biol Sci Med Sci, 2015)
Whether aging lowers skeletal muscle basal capillarization and angiogenesis remains controversial. To investigate the effects of aging on skeletal muscle capillarization, eight young (YW) and eight aged (AW) women completed 8 weeks of exercise training. The response and relationships of muscle capillarization, interstitial vascular endothelial growth factor (VEGF), and microvascular blood flow to aerobic exercise training were investigated. Vastus lateralis biopsies were obtained before and after exercise training for the measurement of capillarization. Muscle interstitial VEGF protein and microvascular blood flow were measured at rest and during submaximal exercise at PRE, 1-WK, and 8-WKS by microdialysis. Exercise training increased (20%–25%) capillary contacts of type I, IIA, and IIB fibers in YW and AW. Interstitial VEGF protein was higher in AW than YW at rest and was higher in YW than AW during exercise independent of training status. Differences in muscle capillarization were not explained by secreted VEGF nor were differences in VEGF explained by microvascular blood flow. These results confirm that aging (57–76 years age range) does not impair the muscle angiogenic response to exercise training, although sex differences may exist in similarly trained women and men.